(untitled) (Cadernos de Sociomuseologia, 2021)
Museums of political memory have been dedicated to the education of recent history in countries that suffered with authoritarianism. Simultaneously, they promote the reparation of traumatic memory of victims of State violence. Practical and theoretical work has been done in order to extend the pedagogical activities through the inclusion of testimonies and declarations of witnesses. The photographic image as historical analysis tool helps us understand the late XIX century hegemonic European discourse and the Estado Novo ideology, that oppressed Portugal for 48 years. At the same time, photography has played a significant role in building up a counter-discourse and complementing the struggle of the people. Nowadays, the audiovisual document is an essencial tool in preserving the resistance memory. These recordings, promoted by the Museu Nacional Resistência e Liberdade (MNRL) – National Museum of Resistance and Freedom –, seek to fill up gaps in Portuguese collective memory, placing them in a traumatic memory musealised space that is the Peniche fort, used as political prison. We support the idea that the gathering and the exposition of these individual memories can publicly express recognition of the past injustices, and that its musealisation is an essencial step in breaking historical silencing. It was made a critical analysis of the table of content suggested for the MNRL and an objective analysis of the exposition ’Por Teu Livre Pensamento’ – For Your Free Thinking. It has been observed that, to this moment, the museum narrative still reproduce a celebrative character about the 25th of April, and that despite the inauguration of the memory of the resistance in the Portuguese national museums minor effort has been made to discuss the controversial year of 1975 that draw this country’s politics. Key-words: Photography; Colective Memory; Sociomuseology; National Museum of Resistance and Freedom;